الفهم التركيبي الدلالي للغة الشفهية لدى الطفل الأصم الحامل للمعين السمعي دراسة مقارنة ال11 حالة بمدرسة الاطفال المعاقين بصريا بمدينة الجلفة - صفاء بن عسلون; مسيلي الأميرة سميحة; السعدية زروق (My University, 2023)
This study aimed at identify the synthetic-semantic oral understanding of the oral language of the deaf child who has a hearing aid and the child who does not have a hearing aid in the school for visually impaired children in Djelfa. This study started from formulating the following hypotheses: The general hypothesis: There is a difference in the synthetic-semantic understanding between the deaf child who has a hearing aid and the deaf child who does not have a hearing aid. As for the partial hypotheses, they were as follows: 1 -We expect a high degree in the level of synthetic-semantic understanding of deaf children who have hearing aids. 2 -We expect a low degree in the level of synthetic-semantic understanding of deaf children who do not have a hearing aid. In order to investigate the hypotheses, the synthetic-semantic understanding test was applied to a sample of 11 children, 5 of the sample have a hearing aid and 6 did not have a hearing aid. Through the obtained results, we deduced the followings There is a difference in the synthetic semantic understanding of the deaf child who has a hearing aid and the one who does not have a hearing aid. 1 -A high degree in the level of synthetic-semantic understanding of deaf children with hearing aids. 2- A low degree in the level of synthetic-semantic understanding among deaf children who do not have the hearing aid. Keywords: synthetic-semantic oral understanding - deaf child – hearing aids